Efeitos do envelhecimento no atendimento fonoaudiológico de uma paciente afásica: um estudo de caso - Segantin, Bianca Isis (2011)
I have always wondered about the reception of aphasic patients in speech therapy clinic: about whether (and how) the establishment of aphasia that undoubtedly weakens the human existence, would involve the specifics if the subject were experiencing the entry in the old age. The aphasia is "talk in suffering that hurts the subject" (FONSECA, 1995, 2002). The subjective drama that is imposed to the aphasic is related to the difficulty of sustaining itself as a speaker facing each other. To that extent, the aphasia can lead to isolation and to the weakening of social ties. The issue that involves the discussion about the weakening of old age is current in the reflection of Gerontology, although the dominant trend is to approach it through the body. In view of my clinical experience, I recognized the need to discuss this concept in a perspective that takes into account the notion of "body inhabited". Clarify, then, the objectives that guided the implementation of this master s thesis: I) to investigate the link between aphasia and old age with the theme underlying the debate a reflection on the polarity of health/ disease in the aging process; II) To discuss the specificity of the notion of weakness when what is at stake is the incidence of aphasia in old age; III) To raise points relating to the necessary convergence between clinical and nonclinical interventions in the care of elderly; IV) To explore the concept of clinical in Social Gerontology. To do this, I realized (1) a literature review of studies that deal with the concepts of health, illness and fragility both in the field where they were forged (medicine) and in Gerontology. Depending on the issue problem that motivate this study, was also concerned; (2) a thorough reading of theoretical clinical perspective of aphasia enacted in research groups (CNPq) "Acquisition, pathologies and language Clinic" (coordinated by profas. Dras. Maria Francisca Lier-DeVitto and Lucia Arantes, LAEL-PUCSP) and "The weakening of old age and the Clinical Practice in the field of Gerontology" (coordinated by profa. Dra. Suzana Carielo da Fonseca). With this specific training, I revisited the serving Lady d. speech therapies that several times made me wonder how much particulars on the aging process and elaborations on it might be involved in the demands and expectations that she told me. Inquiry that included the need for clarification about the nature of the clinical management of something that indeed exceeded the request of D. to get rid of the symptoms in language. That is to say that if changes have been operated by the crossover effect of clinical care with the effects of participation of Ms. D. in social inclusion programs of the treatment Center to aphasics (Caaf- DERDIC/PUCSP), they don t imply the reversibility of the symptomatic condition. All these issues were discussed from the link of the review of relevant literature to the subject (Chapters I, II and III with the case study , as a methodological option. At the end, I take this research endeavor the possibility of to grasp specificities that particularize the clinical practice in the field of gerontology